Reduced intensity conditioning with fludarabine, busulfan and anti-T lymphocyte globulin (FluBu3ATLG) for older patients with myeloid disease: determinants of outcome and the role of cytokine-based predictive modelling - Armstrong, Christopher (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Fludarabine, busulfan and anti-T lymphocyte globulin (FluBu3ATLG) for reduced intensity conditioned (RIC) haematopoietic stem cell transplantation is an established regimen for older patients with myeloid disease. We examined the performance of this combination in modern practice in 175 sequentially treated patients at the National Adult Stem Cell Transplant Programme in Ireland. We furthermore report the clinical correlation and secretion patterns of a 10-cytokine panel measured at serial transplant time-points in a subgroup of 32 patients. 2-year overall survival (OS) was 72.3% and the median follow-up was 23.2 months. Non-relapse mortality was modest at 12.1% by 2-years. The cumulative relapse incidence at 2-years was 29.5% and advancing age was not associated with adverse outcome, including those over the age of 70. The use of ATLG resulted in low levels of severe acute (11.2%) and chronic GVHD (17.3%) and higher doses of ATLG did not associate with excess relapse risk, however it did lead to a protracted T cell immune reconstitution. Predictors of relapse included use of stem cell graft cryopreservation and higher graft T cell content (p=0.004) but increasing donor age had no effect on survival or relapse. Relapse was significantly reduced in those with mixed donor chimerism by adopting a liberal pre-emptive donor lymphocyte infusion strategy (DLI) (p=0.01) and DLI improved survival length after post-transplant relapse (p=0.03). The EASIX score complements this regimen by predicting OS (p=0.01), NRM (p=0.03) and moderate-severe GVHD (p=0.04) at the pre-transplant time-point, moderate-severe GVHD at day 0 (p=0.03), OS from onset of GVHD (p=0.01) and OS and relapse at 1-year post-transplant (p=<0.001, p=0.01). Serial cytokine monitoring in a selection of 32 participants identifies trends in cytokine expression and demonstrated a potential role in predicting outcomes including survival and GVHD. Temporal relationships between IFNγ, IL-12p70, IL-17A and survival, IL-12p70 and IL-17A and relapse and IFNγ, IL-2, IL-6 and IL-10 with GVHD offer insight into the inflammatory secretome and its evolution through transplant. Early increased levels of IFNγ, IL-1β, IL-2, IL-6 and IL-17A, and reduced IL-4 demonstrate associations with acute organ-specific GVHD subtypes and have strong potential as predictive biomarkers. These adjunctive measures offer individualized decision support, and alongside tactical use of DLI allow for an increasingly personalised approach to alloSCT. FluBu3ATLG supported by modern supportive care is well tolerated by older patients, with modest toxicity and favourable long-term outcomes, and most importantly demonstrates the potential for further optimization supported by these data and guided by rationally designed clinical trials.
APPROVED